Optimalisasi Kualitas Jaringan Internet Menggunakan Web Proxy Berbasis WLAN Dengan Metode Penjadwalan (Studi Kasus Di SMK Negeri 1 Bandar Sei Kijang Kabupaten Pelalawan) - Abu Hanifah; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This study aims to determine the optimization of the quality of the internet network using a WLAN-based Web Proxy with the scheduling method at SMK Negeri 1 Bandar Sei Kijang, Pelalawan Regency. This study uses the Action Research method, which was carried out in 2021. The measurement of internet network quality refers to the TIPHON standard with QoS parameters consisting of Throughput, Delay, Jitter, Packet Loss using the Wireshark application. This study uses the Action Research method through diagnosing, action planning, action taking, evaluating, and learning. The subject of this study is all students of class XI, which consists of eight study groups with a total of 219 students. The measurement and calculation of the quality of the internet network were carried out in two groups. The first group consists of four classes before using a WLAN-based web proxy with scheduling method and the second group after using a WLAN-based web proxy with scheduling method. The results of measurements and calculations show that using a WLAN-based web proxy with a scheduling method can optimize the quality of the internet network at SMKN 1 Bandar Sei Kijang. Before using WLAN-based Web Proxy with scheduling method the average index is 1.75 in the Poor category, but after applying the average index increases to 3.75 with the Satisfactory category. Keywords: Optimization, network, internet, proxy, scheduling